2018
DOI: 10.3389/fimmu.2018.01379
|View full text |Cite
|
Sign up to set email alerts
|

RIG-I-Like Receptors as Novel Targets for Pan-Antivirals and Vaccine Adjuvants Against Emerging and Re-Emerging Viral Infections

Abstract: Emerging and re-emerging viruses pose a significant public health challenge around the world, among which RNA viruses are the cause of many major outbreaks of infectious diseases. As one of the early lines of defense in the human immune system, RIG-I-like receptors (RLRs) play an important role as sentinels to thwart the progression of virus infection. The activation of RLRs leads to an antiviral state in the host cells, which triggers the adaptive arm of immunity and ultimately the clearance of viral infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 87 publications
(79 reference statements)
3
46
0
Order By: Relevance
“…In addition, we investigated how specific intracellular signaling pathways drive synergistic innate immune responses through TLR4 and TLR9 crosstalk. This synergistic phenomenon has been identified in multiple reports by our group and others (7,21,31,38). CpG-Dual PLPs also showed CpG density-dependent IL27 response similar to IL12p70, suggesting activation and secretion of multiple cytokines from IL12 cytokine families.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In addition, we investigated how specific intracellular signaling pathways drive synergistic innate immune responses through TLR4 and TLR9 crosstalk. This synergistic phenomenon has been identified in multiple reports by our group and others (7,21,31,38). CpG-Dual PLPs also showed CpG density-dependent IL27 response similar to IL12p70, suggesting activation and secretion of multiple cytokines from IL12 cytokine families.…”
Section: Discussionsupporting
confidence: 77%
“…For emerging vaccines consisting of recombinant proteins, peptides or nucleic acids, various PAMPs are being investigated as adjuvants. The triggering of Toll-like receptors (TLRs) on cell membranes and endosomes, and RIG-I like receptors and cGAS-STING receptors in the cytoplasm, induces potent immunity (6)(7)(8)(9). Although pathogens carry multiple PAMPs and antigens within a unified structure, most vaccine research with PAMPs historically has involved investigations of antigens with independent soluble adjuvants.…”
Section: Introductionmentioning
confidence: 99%
“…Initial attempts to use synthetic RNA as immunostimulants to improve human health were performed using polyinosinic:polycytidylic acid [poly(I:C)] or derivatives, but with limited success [4]. With the advancement of knowledge about the mechanisms of ligand recognition and function of RLRs, the possibility of using RLR ligands as pan-antivirals, vaccine adjuvants, and antitumor agents has gained much attention [5]. While studies using RIG-I RNA agonists are accumulating, Recent research has unveiled divergences in the functions mediated by RIG-I and MDA5; additional knowledge will be necessary to make an informed choice of the most appropriate ligand-based strategy for specific therapeutic or prophylactic clinical applications.…”
Section: The Immunomodulatory Functions Of Rig-i-like Receptors (Rlrsmentioning
confidence: 99%
“…The available data hold great promise for the use of specific RIG-I and MDA5 ligands as novel pan-antivirals, vaccine adjuvants, or potentiators of anticancer immunotherapies [5,59], but they also highlight a knowledge gap and challenges that remain to be addressed. Many studies have reported the use of RIG-I ligands in preclinical studies, but specificity for RIG-I over MDA5 and Toll-like receptors (TLRs) has only been demonstrated for the agonists discussed hereafter.…”
Section: Targeting Rlrs For Therapeutic and Prophylactic Strategiesmentioning
confidence: 99%
“…Insertion of different bases at the position 9 of hairpin RNA result in different levels of activation 3.8 Cell based assay comparing 3p10LG9, 3p10LA9 and 3p10L 3.9 HDX-MS captures stronger allosteric effects upon 3p10LG9 binding to RIG-I than 3p10L Cell based assay in THP1-Dual™ 4. 4 Purification of MS2 VLP 4.5…”
mentioning
confidence: 99%